Amniotic membrane: Alternative transplantation therapy (Research, Society and Development, 2022)
The amniotic membrane is the innermost layer of the three fetal placental membranes. The capture of the amniotic membrane for allograft also occurs during childbirth, soon after negative results of HIV, VDRL, HBsAg and Hepatitis C serologies of the donor mother. The membrane has several properties, such as antibacterial, anti-adhesive, anti-pain, anti-inflammatory, anti-apoptotic effect. In addition, it is highly rich in substances that promote cell proliferation and development. A unique characteristic of the amniotic membrane is that it does not induce immune rejection, because does not express HLA-A, B or DR 5 histocompatibility antigens. Transplanted tissue can be used in the therapy of eye surface diseases, repair of burns or for reconstruction of skin structures. In addition, there are studies testing other possibilities of use for this tissue. After analysis of the research, it was possible to verify that amniotic membrane transplantation consists of a promising alternative therapy, related to the most diverse systems in order to promote efficient and satisfactory results in each of them.